Highly efficient moisture-enabled electricity generation from graphene oxide frameworks. Issue 3 (9th February 2016) - Zhao, Fei; Liang, Yuan; Cheng, Huhu; Jiang, Lan; Qu, Liangti
Abstract : A high performance chemical potential energy harvester for directly generating electric power has been developed on the basis of the three-dimensional assembly of graphene oxide with an oxygen gradient. Abstract : A high-performance power generator has been successfully fabricated based on a superhydrophilic three-dimensional assembly of graphene oxide. The open framework of this specially designed graphene oxide assembly largely facilitated the diffusion of water molecules to produce the dissociated charged ions as free carriers. Meanwhile, its asymmetrical oxygen-containing groups enabled an ionic gradient to accelerate the directed transport of the ionic charge carriers. A high power density of ca. 1 mW cm −2 and an energy-conversion efficiency of ca. 52% were achieved and its potential as a practical power source was evidenced by a simple pendulum-based chemical potential energy harvesting system.